Tracing the occurrence of ocean sciences issues in Greek secondary education textbooks - MOGIAS, ATHANASIOS; BOUBONARI, THEODORA; KEVREKIDIS, THEODOROS (Mediterranean Marine Science, 2022)
This study aims to investigate the presence of ocean sciences issues in Greek secondary education (grades 7-12) science textbooks, in respect of the Ocean Literacy Framework. Content analysis was undertaken concerning both textual and pictorial materials of the Biology, Chemistry, Physics, and Geography – Geology courses. Results revealed that the textbooks under study contain limited and fragmented information with regard to the seven essential principles of the framework, while a comparison with the Ocean Literacy Scope & Sequence evidences inconsistencies. The suggestions arising from this study could help curriculum designers, textbook authors, marine educators, and marine scientists to cooperate on a wider scale towards the inclusion of ocean literacy topics into national curricula worldwide.